Availability and transformation of rock phosphates in three forest soils from southern Nigeria - Juo, A.S.R.; Kang, B.T. (Informa UK Limited, 1978)
The initial effectiveness of two rock phosphate samples from Morocco (MRP) and North Carolina (NCRP) was compared with concentrated superhposphate (CSP) in greenhouse using two Alfisols and one Ultisol from southern Nigeria.